Optimistic income expectations and meeting those expectations: What matters for well‐being in a developing country?. (25th July 2022) - Fan, Sha; Mahadevan, Renuka
Abstract: This paper examines the impact of income expectations and the extent to which these expectations are met, on subjective well‐being. For the Indonesian sample, expectations had asymmetric effects on well‐being, with pessimistic expectations having a strong adverse effect compared with a weak positive effect of optimism. Optimism improves only females' and not males' well‐being while pessimism has the reverse effect on both genders' well‐being. Although unmet expectations reduced well‐being for all subgroups, the mediating role of social capital to negate this was limited to some subgroups. Results point toward a gendered policy agenda and the rural–urban divide to improve well‐being.